To determine whether a number is rational or irrational, we need to determine if it can be written as a fraction.
Looking at the given options:
- √28 is not a rational number because it cannot be simplified to a fraction.
- √36 is a rational number because it simplifies to 6, which is a whole number.
- √40 is not a rational number because it cannot be simplified to a fraction.
- √80 is not a rational number because it cannot be simplified to a fraction.
Therefore, the rational number between 5 and 8 is √36, which simplifies to 6.
Which of the following is a rational number between 5 and 8?
\sqrt{ 28}
\sqrt{36 }
\sqrt{40 }
\sqrt{ 80}
11 answers
Which of the following is using the Product Rule for Exponents correctly?(1 point)
Responses
5^3×5^7=5^21
12^6×12^−5=12
8^2×8^10=16^12
32^6×32^3=32^3
Responses
5^3×5^7=5^21
12^6×12^−5=12
8^2×8^10=16^12
32^6×32^3=32^3
The correct answer is: 32^6 × 32^3 = 32^9.
This is an example of using the Product Rule for Exponents correctly because the bases (32) are the same in both terms being multiplied, and the exponents (6 and 3) are added together to give a final exponent of 9.
This is an example of using the Product Rule for Exponents correctly because the bases (32) are the same in both terms being multiplied, and the exponents (6 and 3) are added together to give a final exponent of 9.
what is the answer
The correct answer is:
32^6 × 32^3 = 32^9
32^6 × 32^3 = 32^9
Simplify using Exponent Rules: 7^4×7×7^13×7^−20
28^−2
17/^2
17/^3
17/−2
28^−2
17/^2
17/^3
17/−2
To simplify the expression 7^4 × 7 × 7^13 × 7^(-20) using exponent rules, we can combine the like bases and add the exponents:
7^4 × 7 × 7^13 × 7^(-20) = 7^(4+1+13+(-20))
Simplifying the exponents:
7^4 × 7 × 7^13 × 7^(-20) = 7^(-2)
Therefore, the simplified form is 7^(-2).
7^4 × 7 × 7^13 × 7^(-20) = 7^(4+1+13+(-20))
Simplifying the exponents:
7^4 × 7 × 7^13 × 7^(-20) = 7^(-2)
Therefore, the simplified form is 7^(-2).
waht is the answer
The answer is 7^(-2).
2(x+5)=32
To solve the equation 2(x+5) = 32, we can follow these steps:
1) Distribute the 2 to both terms inside the parentheses:
2 * x + 2 * 5 = 32
2) Simplify the expression:
2x + 10 = 32
3) Subtract 10 from both sides to isolate the term with x:
2x + 10 - 10 = 32 - 10
This simplifies to:
2x = 22
4) Divide both sides by 2 to solve for x:
(2x)/2 = 22/2
This simplifies to:
x = 11
Therefore, the solution to the equation 2(x+5) = 32 is x = 11.
1) Distribute the 2 to both terms inside the parentheses:
2 * x + 2 * 5 = 32
2) Simplify the expression:
2x + 10 = 32
3) Subtract 10 from both sides to isolate the term with x:
2x + 10 - 10 = 32 - 10
This simplifies to:
2x = 22
4) Divide both sides by 2 to solve for x:
(2x)/2 = 22/2
This simplifies to:
x = 11
Therefore, the solution to the equation 2(x+5) = 32 is x = 11.